Let m be (-5)/((-5)/3) - 1. Let y = m - 2. Solve 0 = 2*a - y*a - 4 for a.
2
Let g = -1 - -9. Solve -3*c + g*c - 5 = 0 for c.
1
Let q be 14⁄4 + (-1)/2. Suppose -3*m = -4*m + q. Solve 0 = 2*f - m*f for f.
0
Let i be 35⁄4 + 2⁄8. Let w(j) = 6*j3 - j2 + 1. Let o be w(1). Let g(l) = l**2 - 3*l - 1. Let z be g(4). Solve -o - i = z*b for b.
-5
Let n be (-8)/(-20) - (-14)/(-10). Let x be (n*1)/(3/(-15)). Solve 0 = -x*o + 8 - 28 for o.
-4
Suppose 4*i + 5*r + 930 = 8*i, 3*r = i - 236. Let v be 4⁄18 - i/(-18). Suppose 0 = -0*n - 5*n + 20. Solve n*q + 1 = v for q.
3
Let y(x) be the second derivative of x5⁄20 - x4⁄2 - 4*x3⁄3 + 5*x2⁄2 + 2*x. Let v be y(7). Let j be (-21)/(-9) + v/6. Solve -j*z - 3*z - 20 = 0 for z.
-4
Suppose -2*b = -5*i - 2, b - 1 = 2*i - 0*i. Let o = b + 2. Let r be 3⁄9 - (-5)/o. Solve -r*x = x for x.
0
Let l be (-2*3)/(1/(-1)). Suppose 4*s + 3*c - 20 = 0, -s + c = 2*s - 2. Suppose j - l = -s. Solve -j*m + 3*m - 3 = 0 for m.
-3
Suppose 10*g = 71 + 99. Solve -5*l + 3 = -g for l.
4